So you want to be a teacher: what are your reasons? - Bakar, Ab. Rahim; Mohamed, Shamsiah; Suhid, Asmawati; Hamzah, Ramlah (Canadian Center of Science and Education, 2014)
This study explored student teachers views of factors influencing them to choose teaching as a career. A total of 600 student teachers completed a questionnaire. They were asked to rate the importance of 25 factors in influencing their choice of teaching as a career. Using Factor Analysis, we categorized the 25 factors into three main factors (Intrinsic, Extrinsic, and Altruistic). We found that of the three factors, altruistic motivation seems to be more dominant (Mean=6.07) than intrinsic (Mean=5.72), and extrinsic motivation (Mean=5.4). We compared the views expressed by those who were not considering teaching and those who were considering teaching as a career option in relation to factors important in influencing their decisions. We also compared the importance of the factors based on gender. For all the groups regardless of gender or career option, altruistic factors were rated more important than intrinsic and extrinsic factors.